A new species and new records of plant mites of Bulnesia arborea ZYGOPHYLLACEAE) from Venezuela - Flechtmann, Carlos; Vásquez, Carlos (Boletín del Centro de Investigaciones Biológicas)
Tetra tarabanensis n. sp. (Prostigmata: Eriphyidae) is described from leaf galls of Bulnesia arborea (Jacq.) Engl. (Zygophyllaceae). The predaceous mite (Phytoseius woodburyi) and the false spider mite (Brevipalpus phoenicis) are reported for the first time from the same host plant in Venezuela.